2021
DOI: 10.1155/2021/6639649
|View full text |Cite
|
Sign up to set email alerts
|

Multilane Microscopic Modeling to Measure Mobility and Safety Consequences of Mixed Traffic in Freeway Weaving Sections

Abstract: Weaving sections are components of highway networks that introduce a heightened likelihood for bottlenecks and collisions. Automated vehicle technology could address this as it holds considerable promise for transportation mobility and safety improvements. However, the implications of combining automated vehicles (AuVs) with traditional human-driven vehicles (HuVs) in weaving freeway sections have not been quantitatively measured. To address this gap, this paper objectively experimented with bidirectional (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…More recently, Ng et al ( 8 ) and Seraj et al ( 9 ) attempted to predict DLCs at the leftmost lanes of a road segment. The sites considered in those studies were sufficiently far away from any ramp influence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Ng et al ( 8 ) and Seraj et al ( 9 ) attempted to predict DLCs at the leftmost lanes of a road segment. The sites considered in those studies were sufficiently far away from any ramp influence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modelling has also demonstrated that key benefits of CAVs such as reduced collisions and increased throughput can vary according to highway geometry, the ratio of autonomous to human-controlled vehicles, and to the manner in which vehicle algorithms form 'platoons' and the headway between them. 9 In real world, rather than laboratory, conditions, such factors will vary so widely that the precise safety outcomes of CAVs may be very difficult to predict.…”
Section: Cavs: a Road Safety Paradox?mentioning
confidence: 99%
“…Like previous studies [23][24][25][26][37][38][39][40], this study undertook the simulation by developing a set of micro-simulation models using PTV Vissim. The US FHWA Surrogate Safety Assessment Model (SSAM) is used to assess the safety performance of platooned HCVs on freeway merge areas [41,42].…”
mentioning
confidence: 99%